2020
DOI: 10.5530/pj.2020.12.169
|View full text |Cite
|
Sign up to set email alerts
|

Caesalpinia sappan L. Wood is a Potential Source of Natural Phosphodiesterase-1 Inhibitors

Abstract: Introduction: A decrease in cAMP and cGMP levels in the brain is linked to human cognitive problems. The degradation of cellular cAMP and cGMP is attributed to phosphodiesterases (PDEs), which constitute a superfamily of enzymes. The inhibition of PDE1 is a promising mechanism to increase cAMP and cGMP levels associated with cognitive disorders. Caesalpinia sappan L. (CS) wood is a natural coloring agent usually consumed as a traditional refreshment or drink by people in Yogyakarta, Indonesia. However, scienti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…RMSD is a distinctive characteristic that demonstrates the capacity of both native ligand complexes and proteins to duplicate themselves in the development of an appropriate configuration. The preferred RMSD value is 1 Å, though 2 Å is also appropriate [ 215 ]. Sixty-three compounds were tested against PDB4B (PDB ID: 4KP6) by performing their molecular docking with MOE.…”
Section: Discussionmentioning
confidence: 99%
“…RMSD is a distinctive characteristic that demonstrates the capacity of both native ligand complexes and proteins to duplicate themselves in the development of an appropriate configuration. The preferred RMSD value is 1 Å, though 2 Å is also appropriate [ 215 ]. Sixty-three compounds were tested against PDB4B (PDB ID: 4KP6) by performing their molecular docking with MOE.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous plants in the literature specifically target PDE1 in the brain ( Helmi et al, 2020a ). Certain plants have been found to be successful candidates for inhibiting the activity of PDE1 ( Helmi et al, 2020b ). Active compounds from plants that inhibit PDE1 are shown in Figure 7 , and their details are given in Table 2 .…”
Section: Pde1 Inhibition and Natural Productsmentioning
confidence: 99%
“…Numerous reports have shown that C. sappan has antioxidant, antibacterial, antidiarrheal, antiinflammatory, anticancer, hepatoprotector, and antidiabetic activities. C. sappan has been scientifically documented to enhance cognition via PDE1 inhibition ( Table 2 ) ( Helmi et al, 2020a ; Helmi et al, 2020b ).…”
Section: Pde1 Inhibition and Natural Productsmentioning
confidence: 99%
See 2 more Smart Citations